Total productive maintenance for the sewing process in footwear - John Reyes; Kevin Alvarez; Amanda Martínez; Juan Guamán (Journal of Industrial Engineering and Management (JIEM), 2018)
Purpose: This research proposes an implementation model of Total Productive Maintenance (TPM) based on the analysis of criticality of machines in the sewing process in the Ecuadorian footwear industry and the identification of unproductive times caused by labor failures. Design/methodology/approach: The project uses field research, presents a quantitative approach, the data collection is done in a horizon of 8 months in which the information is condensed in data tables and takes as a case study one of the most successful companies in the Ecuadorian footwear industry for its initiative to innovate their processes and research new technologies that help increase their efficiency. Findings: The results allow to demonstrate the successful application of the proposed model in the industrial sector of footwear with an increase of average production standards of 5% and a reduction in the number of human errors of 72.2%. Practical implications: The model allows to execute several activities in four phases: preparatory, introduction, implementation and consolidation in order to develop TPM in sewing process. Originality/value: The paper describes a case study in a major shoe company with the aim of reducing the times for unscheduled stoppages and the number of failures.
Keywords: 650; TMP; footwear; shoe company; industry